ESTUDO DE CASO DE PROGRAMA DE FIDELIZAÇÃO EM UMA EMPRESA DO SETOR DE HOTELARIA - Araújo, Alexandre José Vianna Barbosa de (2004)
This work aims at evaluating the importance and impact of customer loyalty programs in companies quantities and qualitative results, it also proposes some basic criteria applied to the phases of diagnostic, development, implementation and management of these programs. These basic criteria, with emphasis on results, could allow the systematization of a strategic approach to customer loyalty in the Brazilian marketplace, providing basic directives to its management. Through a case study of one of the major hotel conglomerate of the world and its customer loyalty programs in Brazil, this work analyses the best practices on managing these loyalty strategies as a resource of sustainable competitive advantage. Based on nonstructured interviews with executives directly or indirectly in charge of these programs in the company, this study presents and evaluates its strategies, tactics, and objectives, mainly, outcomes in short, medium and long term. Through a recent theoretical revision of this issue, specially considering the concepts and models proposed by Duffy and Reichheld, the practices found out on the case study and its sustainability are evaluated.